Sexuality’s Law - Spindelman, Marc (Columbia Journal of Gender and Law, 2013)
The contemporary history of gay sexuality–the full history–has not been written. Within it, increasingly attested to in various ways, appears an ideology of sexual freedom that has played a significant role in shaping, conditioning, controlling, and defining the sweep of gay sexuality, identity, and social life. This Article describes the ideology of sexual freedom, including its valorization of sexual violence, abuse, and injury, up to and including death, traces the ideology’s implications for HIV/AIDS, and documents its actual operation in theorizing about sexuality by and among gay men in the “high” years of the epidemic. After that, it examines some ways in which the ideology of sexual freedom has shaped some more recent debates about same-sex sex and its proper relation to law, proposing that in a number of ways this ideology has been sexuality’s “tougher and truer law,” more important than the formal legal rules promulgated and enforced by the political State. In consequence, it is suggested, efforts to understand and address same-sex sexual violence and its consequences both for individuals and society, more generally, need to grapple with the ideology of sexual freedom directly–and not ignore it–if there is to be any realistic hope for the liberal State to satisfy its obligations to protect private individuals against interpersonal harms.